ART IN THE AGE OF ALGORITHMS: SOCIAL CHANGE THROUGH DATA-DRIVEN CREATIVITY - Ukande, Anu; Bharadwaj, Kumkum (International Journal of Research -GRANTHAALAYAH, 2026)
The rapid integration of algorithms, big data, and artificial intelligence into cultural production has fundamentally reshaped contemporary artistic practices. Art in the Age of Algorithms examines how data-driven creativity operates not only as a technological innovation but also as a catalyst for social change. This research explores how artists employ algorithms, machine learning, and computational systems to interrogate power structures, bias, surveillance, identity, and participation in digital societies. The study highlights how artistic engagement with data transforms abstract computational processes into accessible, critical narratives. The paper argues that algorithmic art functions as a socio-political intervention, challenging dominant technological paradigms while fostering public awareness and dialogue around ethical, cultural, and social implications of data-driven systems. Ultimately, this research positions data-driven art as a critical space where creativity, technology, and social responsibility converge, redefining the role of art in shaping collective understanding in the algorithmic era.